An Evaluation of Universal Grammar and the Phonological Mind1 - Everett, Daniel L. (Frontiers in Psychology, 2016)
The article begins by reviewing the history of views of the sources of language and moves on to underscore problems with the "man-in-a-can" view of language, one way that Universal Grammar might be characterized. It moves then to a detailed consideration of the problems that a language without recursion raises for UG and the attempts by UG theorists to answer these problems. Finally, the paper reviews in detail one of the most carefully argued proposals in the UG literature, the Phonological Mind thesis, rejecting this as failing to establish any strong arguments for UG. The conclusion is that if such a carefully worked out set of arguments for UG fails, then, a fortiori, many other weaker arguments are likely to fall through as well.